PERANCANGAN JARINGAN VIRTUAL LAN MENGGUNAKAN METODE PROTOKOL PEER-VLAN SPANNING TREE - Adi Sopian; Khusnul Khoiriyah; Ilham Dwi Putra Gonti (Institut Teknologi dan Bisnis Swadharma, 2022)
The role of computer networks today is very important, starting from the need to share data, software, and communication lines (internet). PT. XYZ is a company engaged in event organizer services. As a modern company, of course, it already has computer network technology to support operational activities. However, along with the increasing needs and users, problems related to security arise and there is no redundancy path between switches. The purpose of this research is to design a VLAN network and create a redundancy path so that it can divide the network segment of each division with broadcast storm prevention technology. Network implementation with Vlan Trunking Protocol to divide network segments between divisions is going well so that there is a backup path between switches so that when one of the lines dies, the network will remain connected